The impact of oil price shocks on economic growth in Algeria - Hafsa DIB (Theoretical and Applied Economics)

(untitled)
This research aims to quantify the impact of oil price shocks on Algeria’s economic growth by employing the novel Dynamic Auto Regressive Distributed Lag (dynardl) approach in conjunction with the Regularized Least Square Kernel (KRLS) method, utilizing annual data spanning from 1970 to 2022. The findings indicate a notable positive influence of oil prices on economic growth, which is similarly observed with government expenditure and population growth. Conversely, the real effective exchange rate and the money supply are found to negatively impact economic growth. Further, the KRLS estimations lend robust support to the outcomes derived from the dynardl model. Analysis of counterfactual oil price shocks on GDP suggests that a positive shock of +10% in oil prices significantly boosts GDP over the long term, whereas a negative shock of -10% conversely results in a long-term decline in GDP.